The Relationship Between Childhood Trauma and Non-Suicidal Self-Injury Behavior in Adolescents with Depression: The Mediating Role of Rumination - Fu W; Li X; Ji S; Yang T; Chen L; Guo Y; He K (Psychology Research and Behavior Management, 2024)
Wenxian Fu,1– 4 Xinyi Li,1– 4 Sifan Ji,1– 4 Tingting Yang,1,3– 5 Lu Chen,1,3– 5 Yaru Guo,1,3– 5 Kongliang He1– 5 1Affiliated Psychological Hospital of Anhui Medical University, Hefei Fourth People’s Hospital, Hefei, 230022, People’s Republic of China; 2School of Mental Health and Psychological Sciences, Anhui Medical University, Hefei, 230022, People’s Republic of China; 3Anhui Mental Health Center, Hefei Fourth People’s Hospital, Hefei, 230022, People’s Republic of China; 4Psychiatry Department, Hefei Fourth People’s Hospital, Hefei, 230022, People’s Republic of China; 5Psychological Counseling department, Hefei Fourth People’s Hospital, Hefei, 230022, People’s Republic of ChinaCorrespondence: Kongliang He, Affiliated Psychological Hospital of Anhui Medical University, Hefei Fourth People’s Hospital, Hefei, 230022, People’s Republic of China, Tel +8613966721862, Email hefei413@126.comObjective: Non-suicidal self-injury (NSSI) behavior is very common in adolescents with depression, and childhood trauma is considered one of the distal risk factors for its exacerbation. Rumination caused by adverse traumatic experiences, which can be transferred through NSSI behavior, can alleviate symptoms of depression in adolescents. The current research focuses on the relationship between the three, further exploring whether rumination is a mediator in the relationship between childhood trauma and NSSI behavior on the basis of previous studies, and provides some suggestions for future early intervention for adolescents with depression.Methods: A total of 833 adolescent patients with depression who met the DSM-5 criteria for depressive episode were recruited from 12 hospitals in China. The Chinese version of the Function Assessment of Self-mutilation, Childhood Trauma Questionnaire, and Rumination Inventory were used as research tools.Results: The scores of childhood trauma and rumination in adolescents with depression in the NSSI group were higher than those in the non-NSSI group. A Pearson’s correlation analysis showed that childhood trauma was positively correlated with rumination (r=0.165, P< 0.01), different types of childhood trauma were significantly positively correlated with rumination and its three factors, and these results were statistically significant. Rumination partially mediated the relationship between childhood trauma and NSSI behavior in depressed adolescent patients (effect size=0.002), and the effect in female participants (effect size=0.003), was greater than that in male participants (effect size=0.002).Conclusion: Childhood trauma and rumination were key factors for NSSI behavior in adolescents with depression. Childhood trauma not only has a direct effect on NSSI behavior in adolescent depression, but also plays an indirect effect on NSSI behavior through rumination.Keywords: adolescents, childhood trauma, rumination, non-suicidal self-injury